NILAI EKONOMI HASIL HUTAN NON KAYU DAN KONTRIBUSINYA TERHADAP PENDAPATAN RUMAH TANGGA (Studi Kasus Pada Dua Desa Sekitar Taman Wisata Sibolangit) - Batubara, Ridwanti; Affandi, Oding (Wahana Forestra: Jurnal Kehutanan, 2017)
People around the Park Tour (PT) Sibolangit develop many NTFPs on land owned. Therefore, this study aims to: (1) find out the types of NTFPs most used by the community, (2) to know the value of NTFPs products, (3) to know the contribution of NTFPs to the income of the community. This research was conducted by survey method and conducted in two selected villages namely Sembahe Village and Bengkurung Village, Sibolangit Sub-district, Deli Serdang Regency. Communities in both research sites developed and utilized NTFPs such as pecan, petai, duku, durian, jengkol, mangosteen, areca nut, nira (aren) water, ginger, temulawak, and others. Most of these NTFPs are commercial (sold). NTFPs that has the greatest potential of water sap. The economic value of NTFPs in Sembahe village reaches Rp. 967.529.300 / year or accounted for about 57.28% of total family income. While the economic value of NTFPs in Bengkurung village reached Rp 509,180,000 / year or accounted for about 65.57% of total household income.